Interrelationships Between Phosphorites And Associated Biologically Productive Hard Bottoms, North Carolina Continental Shelf - Stanley R. Riggs (International Marine Minerals Society, 1992)
Onslow Bay is a broad, shallow, high-energy shelf system bounded by the Cape Lookout and Frying Pan shoals. It is generally a sediment-starved shelf system dominated by hardbottoms with a scattered and discontinuous veneer of mobile Holocene sediments. Phosphate-rich beds of the Miocene Pungo River Formation crop out in a belt 150 km long and up to 50 km wide across the continental shelf in Onslow Bay, North Carolina. Previous research has demonstrated that a few of these beds contain vast quantities of potentially economic phosphate resources that occur in the surface and shallow subsurface sediments. Onslow Bay contains five phosphate-bearing beds predicted to include up to 20.7 billion tons of in-place phosphate concentrate with total sediment grades ranging up to 22.9% P2O5 and adjusted average concentrate grades of 29.8% P2O5. These phosphates are lithologically and chemically similar to phosphates currently being mined in the nearby Aurora phosphate district in North Carolina. Various lithologies of the Pungo River Formation and associated rock units of Oligocene and Quaternary age crop out on the sea floor to form extensive hardbottom habitats that dominate almost 100% of Onslow Bay. A large proportion of these hardbottoms appear to be sea floor deserts, whereas others are virtual oases with rich associations of benthic organisms. These important differences in benthic community structure appear to be greatly influenced by one or more of the following variables: 1) geologic framework (geologic formation, hardbottom composition, morphology, and spatial orientation relative to dominant currents and waves), 2) texture, movement, and accumulation of surface sediments, and 3) flow rates and chemical composition of discharged submarine groundwater.